Togo : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1994)
This paper reviews economic developments in Togo during 1990-94. In 1990, the economic situation deteriorated, with an overall growth of real GDP of only 0.1 percent. Growth in the primary sector decelerated, in comparison with the previous year, largely because of late rains, but remained appreciable (3 percent), despite the decline in the production of food crops. Output in the secondary sector fell by 4.4 percent. In 1991, real GDP contracted by 0.9 percent, marking the beginning of a three-year decline.